Exchange rate regimes and global cocoa trade: to float or to peg? - Bismark Addai; Adjei Gyamfi Gyimah; Kwadwo Poku-Agyemang (Cogent Economics & Finance, 2020)
The effectiveness of different exchange rate systems continues to attract the attention of many scholars, however, most discussions on exchange rate regimes have focused on how the phenomenon affects economic growth, economic stability, financial crises, international tourism, and international trade in general. In this study, we explore the effect of exchange rate regimes that has so far escaped the attention of many scholars in the exchange rate literature, the effect of exchange rate regimes on global cocoa trade. STATA statistical tool was employed in analyzing panel data from 10 leading cocoa-producing countries from 1980 to 2016. With the justification of the Hausman test, the fixed effects estimation method was used. The main effect observed was that countries suffered a statistically significant negative effect on net exports if they pegged their currencies to the Euro, but countries with floating exchange rates regimes do not suffer that effect. Therefore, this study recommends that countries adopt a more flexible exchange rate system, particularly if they are exporters of agricultural raw materials and products. Most cocoa-producing countries grow cocoa as a cash crop, thus, rely heavily on the trade of cocoa beans and other product. Therefore, it would be counterintuitive to have all the profits from the trade of cocoa to be wiped out by the rigidity of an exchange rate regime.
Keywords: F14; F33; 330; exchange rates; regime; peg; float; global; cocoa trade